Antidepressive-like effect of imperatorin from Angelica dahurica in prenatally stressed offspring rats through 5-hydroxytryptamine system. Issue 8 (24th May 2017) - Cao, Yanjun; Liu, Jiahui; Wang, Qiong; Liu, Minghui; Cheng, Ying; Zhang, Xiaoxiao; Lin, Tianwei; Zhu, Zhongliang
Abstract : Adolescence is a time of continued brain maturation, particularly in limbic and cortical regions, which undoubtedly plays a role in the physiological and emotional changes. Prenatally stressed offspring rats were used to investigate the potential antidepressive-like effects of imperatorin (IMP) extracted from the root of radix angelica. After 4 weeks of treatment of IMP, behavioral tests (sucrose-preference test, forced-swimming test, and open-field test) were measured. 5-hydroxytryptamine (5-HT) concentration in the hippocampus and frontal cortex was measured using an enzyme-linked immunosorbent assay. Serotonin transporters (5-HTT) and 5-HT1A receptor (5-HT1A R) mRNA expression in the hippocampus and frontal cortex were also determined by real-time PCR. Administration with IMP (15 and 30 mg/kg/day, intragastrically) for 28 days markedly increased the percentage of sucrose (anhedonia), decreased the immobility time, and increased the number of total crossings, center crossings, rearing, and grooming in the male prenatally stressed offspring. Meanwhile, we found that 5-HT concentration in the hippocampus and frontal cortex was significantly increased in the IMP-treated group. Subsequently, we found significantly decreased 5-HTT and increased 5-HT1A R mRNA expressions in the hippocampus and frontal cortex after IMP treatment in the prenatally stressed male offspring. IMP showed antidepressive-like effects and increased 5-HT concentration in male prenatally stressed offspring, suggesting that IMP could be of therapeutic use in preventing depressive-like behavior in adolescence.